2017
DOI: 10.1038/ncomms15791
|View full text |Cite
|
Sign up to set email alerts
|

Parity-time-symmetric quantum critical phenomena

Abstract: Synthetic non-conservative systems with parity-time (PT) symmetric gain–loss structures can exhibit unusual spontaneous symmetry breaking that accompanies spectral singularity. Recent studies on PT symmetry in optics and weakly interacting open quantum systems have revealed intriguing physical properties, yet many-body correlations still play no role. Here by extending the idea of PT symmetry to strongly correlated many-body systems, we report that a combination of spectral singularity and quantum criticality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
214
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(221 citation statements)
references
References 54 publications
6
214
1
Order By: Relevance
“…Such theoretical predictions have been confirmed experimentally by using optical systems and ultracold atoms [22][23][24][25][26][27][28][29][30]. However, since most of the previous studies dealt with single-particle physics, exploration of many-body physics in NH systems is still in its infancy [3][4][5][6][31][32][33][34].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Such theoretical predictions have been confirmed experimentally by using optical systems and ultracold atoms [22][23][24][25][26][27][28][29][30]. However, since most of the previous studies dealt with single-particle physics, exploration of many-body physics in NH systems is still in its infancy [3][4][5][6][31][32][33][34].…”
mentioning
confidence: 92%
“…NH quantum systems arise when the system undergoes dissipation to an environment [37,38]. It has been revealed that non-Hermiticity drastically alters the properties of a number of quantum phenomena that have been established in the Hermitian physics, such as quantum phase transitions [1][2][3][4], quantum critical behavior [5][6][7], topological phases [8][9][10][11][12][13][14][15][16][17], and magnetism [18]. Such theoretical predictions have been confirmed experimentally by using optical systems and ultracold atoms [22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…Here e x(y) denotes the unit vector for each direction, and the lattice constant is set to unity. When we focus on the short-time evolution, the last term describing the quantum-jump is negligible [61][62][63][64]. In this case, we can see that the timeevolution is described by…”
mentioning
confidence: 99%
“…This can be done by generalizing the variational state to Gaussian density matrices. Another interesting direction is to extend our approach to Markovian open quantum systems subject to dissipation [56,[106][107][108] and measurements [109][110][111][112][113] by employing the variational principle appropriate for master-equation dynamics [114,115]. Generalizing the decoupling canonical transformation, our approach can also be applied to multiple impurities [116] coupled to bosonic environments.…”
Section: Discussionmentioning
confidence: 99%